Hierarchical molecular dynamics of bovine serum albumin in concentrated aqueous solution below and above thermal denaturation. Issue 6 (14th January 2015) - Grimaldo, Marco; Roosen-Runge, Felix; Hennig, Marcus; Zanini, Fabio; Zhang, Fajun; Jalarvo, Niina; Zamponi, Michaela; Schreiber, Frank; Seydel, Tilo
Abstract : Quasi-elastic neutron scattering provides a detailed microscopic picture of the global and internal protein dynamics reflecting thermally induced structural changes. Abstract : The dynamics of proteins in solution is a complex and hierarchical process, affected by the aqueous environment as well as temperature. We present a comprehensive study on nanosecond time and nanometer length scales below, at, and above the denaturation temperature T d . Our experimental data evidence dynamical processes in protein solutions on three distinct time scales. We suggest a consistent physical picture of hierarchical protein dynamics: (i) self-diffusion of the entire protein molecule is confirmed to agree with colloid theory for all temperatures where the protein is in its native conformational state. At higher temperatures T > T d, the self-diffusion is strongly obstructed by cross-linking or entanglement. (ii) The amplitude of backbone fluctuations grows with increasing T, and a transition in its dynamics is observed above T d . (iii) The number of mobile side-chains increases sharply at T d while their average dynamics exhibits only little variations. The combination of quasi-elastic neutron scattering and the presented analytical framework provides a detailed microscopic picture of the protein molecular dynamics in solution, thereby reflecting the changes of macroscopic properties such as cluster formation and gelation.